Anglo-American second wave feminisms: the ethics of heterogeneity - Whelehan, Imelda (1993)
This thesis investigates debates and tensions in Second Wave Anglo-American Feminisms since the sixties. It interrogates claims that feminism is in crisis, and that the term 'feminism' itself is now semantically overburdened. Its chief purpose is to show that despite feminism's heterogeneity, there are central features of feminist politics which offer an oppositional identity to theorists concerned with exposing the way meanings of gender still shape society and academic discourse. The scope of this work extends from early Second Wave writings to current scholarly reflections on the interface between feminist and other critical theories. This study emphasizes that even the apparent 'anti-theory' thrust of early writers stand testimony to an abiding concern with theories of knowledge, power and representation. Even feminism's early antagonism to 'high theory' could be interpreted as a challenge to the means by which 'theory' is constructed.